Networked Optimal Control with Random Medium Access Protocol and Packet Dropouts. (23rd February 2015) - Zhu, Chaoqun; Guo, Ge; Yang, Bin; Wang, Zhiwen
Abstract : This paper is concerned with an optimal control framework for networked control systems in which the channel access of actuators is governed by a group random access protocol. The system is modeled as a switching Markov jump system with multiple modes according to channel-access status of the actuators, and an independent identical distribution Bernoulli process is used to describe the random packet dropouts of the channel. Then, an optimal control design methodology is addressed to satisfy the quadratic cost function by applying the well-developed theory for jump linear systems and stochastic optimal control while guaranteeing the mean-square exponential stability of networked control systems. And, finally, a numerical example is exploited to demonstrate the effectiveness of the proposed method.